The Antioxidant, Antibacterial and Anti-Biofilm Properties of Rapeseed Creamed Honey Enriched with Selected Plant Superfoods - Michał Miłek; Ewa Ciszkowicz; Ewelina Sidor; Joanna Hęclik; Katarzyna Lecka-Szlachta; Małgorzata Dżugan (Antibiotics, 2023)
The aim of the study is to evaluate the effect of the addition of selected fruits and herbs belonging to the “superfoods” category for the bioactivity of a rapeseed honey matrix. Flavored creamed honeys with nine types of various additives (2 and 4% of content) were prepared and analyzed for the content of total phenols, flavonoids, antioxidant (FRAP, DPPH and ABTS) and antibacterial activity against four strains of bacteria. Additionally, the impact of three months of storage on the antioxidant properties of the products obtained was examined. The significant dose-dependent increase in the content of bioactive ingredients and antioxidant capacity in spiced honeys, as compared to control honey, was observed. The highest enrichment was obtained for the addition of powdered sea buckthorn leaves and black raspberry fruits. Honey with the addition of sea buckthorn leaves inhibited the growth of P. aeruginosa, S. aureus and K. pneumonia, whereas honeys with black raspberry and blackcurrant fruits showed activity only on the latter two strains. Furthermore, what is more interesting, honey supplemented with sea buckthorn leaf and black raspberry fruits inhibited S. aureus biofilm formation at the sub-minimum inhibitory concentrations (sub-MICs), showing a dose-dependent anti-biofilm effect.